Global and regional wall motion abnormalities and incident heart failure in the general population. (15th June 2022) - Espersen, Caroline; Modin, Daniel; Platz, Elke; Jensen, Gorm Boje; Schnohr, Peter; Prescott, Eva; Gislason, Gunnar; Møgelvang, Rasmus; Biering-Sørensen, Tor
Abstract: Background: Wall Motion Score Index (WMSI) is a simple method to quantify global and regional systolic function on echocardiography. We sought to investigate the prognostic importance of global and regional WMSI for the development of incident heart failure (HF) in the general population. Methods: We included adults without HF or ischemic heart disease from the 4th Copenhagen City Heart Study (2001–2003). At baseline, participants underwent an echocardiography and physical examination and completed a self-administered health questionnaire. WMSI was assessed by conventional echocardiography using a 16-segment model obtaining WMSI assessments for the anterior, lateral, inferior, septal, and posterior left ventricular (LV) walls and calculating a global WMSI. The primary endpoint was incident HF. Results: Among 3415 participants (mean age 58 years, 42% male, 45% with hypertension), 83 (2.4%) had hypo-, a-, or dyskinesia of at least one LV wall segment at baseline. During a median follow-up of 15.4 years, 297 (8.7%) participants developed HF. After adjusting for important clinical variables, LV ejection fraction and E/A, hypo-, a- or dyskinesia of at least one segment in any of the LV regional walls was associated with a higher risk of incident HF (HR 3.63, 95% CI 2.15–6.12, p  < 0.001). Similarly, global WMSI was independently associated with a higher risk of HF (HR 1.38 per 0.1 increase, 95%CI 1.22–1.56, p < 0.001). Conclusion: Wall motion abnormalities in any regional LV wall and global WMSI were associated with incident HF in this general population cohort independent of various baseline clinical data, LV ejection fraction and E/A. Graphical abstract: Unlabelled Image Highlights: 3, 415 participants from the general population without heart failure or ischemic heart disease were included. Wall motion score index was assessed by echocardiography at baseline using a 16 segment model. 83 participants (2.4%) had hypo-, a-, or dyskinesia of at least one left ventricular segment at baseline. During a median follow-up of 15.4 years (IQR 11.9-16.0), 297 participants (8.7%) developed incident heart failure. Hypo-, a-, or dyskinesia of ≥1 segment in any left ventricular wall was associated with a higher risk of incident heart failure.